Usability and Accessibility Analysis of Government of Websites of Sri Lanka - Kartheeswaran, T.; Gopinath, S.; Lojenaa, N.; Senthooran, V. (IEEE TENSYMP 2016, Bali Indonesia, 2016)
The websites usability and accessibility standards make more convenient to the internet users. The most of exists websites are failed to follow these standards. Hence, in this research study, we analyze the usability and accessibility standards of highly used websites of Sri Lankan government. The forty-seven government websites are selected to investigate the usability and accessibility guidelines. The above-mentioned guidelines were analyzed using standard online web analytical tools such as WAVE, googlePageSpeed insight, google Mobile-Friendly Test, Pingdom tool, and PowerMapper. Further, the results were analyzed using a weighted method to predict the standard level of the websites.
Keywords: W3C; WCAG; WAVE; googlePageSpeed; PowerMapper; Pingdom